Analisis Efisiensi Dan Kehilangan Air Pada Saluran Sekunder D.I Bettu Kabupaten Bulukumba - Kurniadi, Arlan; Badrun, Burhanuddin; Cangara, Satriawati (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
Water is a very important need for life in bum, especially living makhuk such as humans, plants, animals and others. In this case, the fulfillment of clean water to be consumed, both for drinking water and for other needs can be done in various ways, adjusted to existing facilities and infrastructure. This is related to the amount of water loss in the irrigation network caused by evaporation, water intake for other purposes, or leakage along the channel. Based on irrigation planning criteria, the amount of water loss in the irrigation network can be minimized by improving the water management system and improving the physical irrigation infrastructure. So the Bialo secondary channel has an efficiency level of 58% which is still in the good category or still works well to drain water into the tertiary channel. This level of efficiency is supported by the physical building of the bialo secondary canal irrigation which is still in good condition and the Bialo secondary channel although the physical condition of the building is still good, it still experiences water loss caused by evaporation loss and seepage which causes water loss of 0.1368 m3/s. Despite experiencing water loss but still has a level of efficiency that is still in good condition.